The Existence of Al-Awwabien Assembly in Practicing Ratib Al-Haddad Rituals in Palembang City 1985-2008 - Nabilah Julaika Putri; Muhammad Ilmi Luthfi; Syarifuddin; Supriyanto (Criksetra: Jurnal Pendidikan Sejarah, 2022)
This research is described in three main issues of problem formulation, namely; (1). Al-Awwabien Assembly as the organization that spreads Ratib al-Haddad in Palembang City; (2). Characteristics brought by the Al-Awwabien Assembly in the reading of Ratib al-Haddad in Palembang City; (3). Looking for the influence of Ratib al-Haddad on the al-Awwabien congregation in the city of Palembang. The purpose of this research is to explore practicing Ratib Al-Haddad in Al-Awwabien Assembly. This study uses historical methode. Based on data interviews with three informants, namely Habib Ali Karor al-Haddad, Ustadz Abul Hasan Assyadzili and Ustadz Ilyas. The results of this study, as is known, the dhikr of Ratib Al-Haddad is generally practiced by people of Hadramaut Arab descent. After the al-Awwabien assembly founded by KH. Ali Umar Thoyyib in 1985 taught the dhikr of Ratib al-Haddad to the public, slowly became a popular practice outside the Arab descent environment. The type of Ratib al-Haddad reading taught by the al-Awwabien assembly is slightly different from that practiced by the general public, namely the addition of other dhikr. The Al-Awwabien Assembly was very influential on the people of Palembang so that they became more religious.